2022
DOI: 10.3390/rs14215418
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Forecasting Ionospheric foF2 Variation in the Low Latitude Region during Low and High Solar Activity Years

Abstract: Prediction of ionospheric parameters, such as ionospheric F2 layer critical frequency (foF2) at low latitude regions is of significant interest in understanding ionospheric variation effects on high-frequency communication and global navigation satellite system. Currently, deep learning algorithms have made a striking accomplishment in capturing ionospheric variability. In this paper, we use the state-of-the-art hybrid neural network combined with a quantile mechanism to predict foF2 parameter variations under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The authors found that the results obtained with the LSTM model give the best forecasting results.Tang et al (2022)[50] developed a global ionospheric TEC prediction model combining indirect forecasting methods from previous studies with the machine-learning Prophet model(Taylor and Letham, 2018) [51] to forecast a global TEC map for the next two days. The results show that the technique used forecast TEC with good accuracy.Bi et al (2022)[52] successfully used a state-of-the-art hybrid NN combined with a quantile mechanism to forecast foF2 parameter variations under low and high solar activity years including solar-terrestrial physics/space weather events.Reddybattula et al (2022) [53] adopted a long short-term memory (LSTM) DL network model to forecast TEC from GPS signals at a low-latitude location during about eight years of data for training and validation. One year of data was used for independent testing and forecasting of the TEC.…”
mentioning
confidence: 99%
“…The authors found that the results obtained with the LSTM model give the best forecasting results.Tang et al (2022)[50] developed a global ionospheric TEC prediction model combining indirect forecasting methods from previous studies with the machine-learning Prophet model(Taylor and Letham, 2018) [51] to forecast a global TEC map for the next two days. The results show that the technique used forecast TEC with good accuracy.Bi et al (2022)[52] successfully used a state-of-the-art hybrid NN combined with a quantile mechanism to forecast foF2 parameter variations under low and high solar activity years including solar-terrestrial physics/space weather events.Reddybattula et al (2022) [53] adopted a long short-term memory (LSTM) DL network model to forecast TEC from GPS signals at a low-latitude location during about eight years of data for training and validation. One year of data was used for independent testing and forecasting of the TEC.…”
mentioning
confidence: 99%